Community pharmacists provided telephone treatment support for patients who received long-term prescribed medication - Yamamoto N; Nitta M; Kamei M; Hara K; Watanabe F; Akagawa K; Kurata N (Dove Medical Press, 2016)
Nobuo Yamamoto,1 Mitsuyo Nitta,1 Miwako Kamei,2 Kazuo Hara,1 Fumiyuki Watanabe,2 Keiko Akagawa,1 Naomi Kurata1 1Division of Community Healthcare and Pharmacy, Department of Healthcare and Regulatory Sciences, Showa University School of Pharmacy, Tokyo, Japan; 2Division of Health Communication, School of Pharmacy, Nihon University, Chiba, Japan Purpose: This study was conducted to evaluate whether a community pharmacist’s assistance during the treatment of a patient with a chronic illness would help to discover and improve issues regarding the treatment. Method: We employed a prospective intervention study with a control group. The patients ranging in age from 60 to 74, were using one of the six selected community pharmacies in the Tokyo metropolitan area. They had been prescribed six or fewer kinds of medications, one of which was amlodipine. The medication dosages covered 1 month or longer. Patients who agreed to participate in the study were randomly assigned to the groups at each pharmacy. For the patients in the intervention group, the pharmacists provided telephone counseling between physician visits, in addition to the time they visited the pharmacies to collect their medications. For the patients in the control group, the pharmacists provided counseling only at their pharmacies. Results and discussion: The average days of medication administration were 49.2 days for the 58 patients in the intervention group, and 49.8 days for the 53 patients in the control group, with the average number of medications being 3.4 items per person for both groups. Through the telephone counseling, we were able to collect more information, eg, changes in physical condition and occurrences of side effects, from the intervention group than from the control group. The rate of incident detection in the information from the intervention group was five times that of the control group, making subsequent incident resolutions faster. Conclusion: This study suggested that phone counseling between physician visits could enable the identification of more issues regarding patients’ conditions. Keywords: community pharmacy, outpatient, long-term dosage, telephone assistance